1981
DOI: 10.1088/0029-5515/21/1/010
|View full text |Cite
|
Sign up to set email alerts
|

A study of exploding-pusher laser-induced implosions using X-ray backlighting

Abstract: 1.3-keV X-ray backlighting of microballoons imploded with 0.8-TW, 50-ps Nd-glass-laser pulses has been performed early during the irradiation. Transmission measurements have been interpreted in terms of fast-electron energy deposition. Targets with the thinnest walls are shown to be pre-heated up to more than 200 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…On the other hand, suprathermal electrons attributed to resonance absorption [7], lead to target pre-heating. This effect has been deduced from hard-X-ray spectra [2,8], K a line radiation in multi-layered targets [9] or, more recently, from X-ray backlighting of coated glass microballoons [10]. Both thermal flux inhibition and fast-electron pre-heat are required in numerical simulations and scaling models for exploding-pusher experiments [1][2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…On the other hand, suprathermal electrons attributed to resonance absorption [7], lead to target pre-heating. This effect has been deduced from hard-X-ray spectra [2,8], K a line radiation in multi-layered targets [9] or, more recently, from X-ray backlighting of coated glass microballoons [10]. Both thermal flux inhibition and fast-electron pre-heat are required in numerical simulations and scaling models for exploding-pusher experiments [1][2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…The experiments were performed with a pulse duration of 500 ps. Other results obtained at 50 and 200 ps and published elsewhere [7,35,45] will be referred to during the discussion. The characteristics of the more representative imploded targets, together with the nominal value of the laser irradiance on target 0i, are reported in Tables II and III.…”
Section: Fig5 Pinhole Camera Photograph Of Time-integrated X-ray Emis...mentioning
confidence: 98%
“…Numerous studies [38] have shown that the classical thermal flux expression: q=-xVT e (5) where x « T | / 2 is not applicable when the characteristic length of the thermal gradient reaches the order of the electron-ion mean free path or when the flux value given by expression (5) is greater than the free-streaming theoretical limit: = 0 . 6 4 n e k T e m e 1 / 2 (6) To keep a local formulation, it is assumed that the effective electron heat flux is given by the usual harmonic mean formula: (7) where qL = fqFS> i-e -the limit flux is reduced below the classical free-streaming value by a factor f which can be adjusted from numerical simulation. Usually, f is kept constant and equal to 5 X 10~2.…”
Section: Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The first experiments with a 1.06 jitm laser beam were directed at the exploding pusher regime, governed at this wavelength by suprathermal electrons, and its behaviour in the case of large irradiance defects. A direct measurement of shell heating was achieved by X-ray backlighting [20]. The transition to a more ablative regime in the laser range of 0.6 TW/500 ps was analysed with DT-filled microballoons coated with a plastic ablator of variable thickness [2.1 ]; the analysis was based on the evolution of preheat, hydrodynamic efficiency and density/ temperature performances (Fig.…”
Section: Laser-matter Interactionmentioning
confidence: 99%